Sex and Age Differences in Anxiety and Depression Levels Before and After Aerobic Interval Training in Cardiac Rehabilitation. Issue 1 (January 2022) - O'Neill, Carley D.; Vidal-Almela, Sol; Terada, Tasuku; Kamiya, Kentaro; Tulloch, Heather E.; Pipe, Andrew L.; Reed, Jennifer L.
Abstract : Purpose: The objective of this study was to investigate sex and age differences in anxiety and depression among patients with cardiovascular disease at baseline and following aerobic interval training (AIT)-based cardiac rehabilitation (CR) and secondarily to compare dropout rates between sexes and age groups. Methods: Participants were younger (⩽44 yr), middle-aged (45-64 yr), and older adults (≥65 yr). The AIT protocol consisted of: 4 × 4-min of high-intensity work periods at 85-95% peak heart rate (HR) interspersed with 3 min of lower-intensity intervals at 60-70% peak HR, twice weekly for 10 wk. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale at baseline and following CR. Results: At baseline, of 164 participants (32% female), 14 (35% female) were younger, 110 (33% female) were middle-aged, and 40 (30% female) were older. Older adults reported lower anxiety levels versus younger (4.4 ± 2.6 vs 7.8 ± 3.4 points, P = .008) and middle-aged adults (4.4 ± 2.6 vs 6.1 ± 3.6 points, P = .05). Baseline depression levels did not differ between age groups ( P = .749). All age groups experienced a reduction in anxiety (younger =−2.67; middle-aged =−1.40; older =−0.85) and depression (younger =−1.50; middle-aged =−0.83; older =−0.70) levels following CR. Differences in dropout rates were observed between age groups (χ 2 [1] = 13.4, P = .001). Within each age group, 43% (female n = 2, male n = 4) of younger, 10% (female n = 8, male n = 3) of middle-aged, and 2.5% (female n = 0, male n = 1) of older participants dropped out. Conclusions: Younger and middle-aged adults experience higher levels of anxiety upon entry into CR compared with older adults. Cardiac rehabilitation was associated with significant reductions in anxiety and depression severity, yet dropout rates were highest among younger adults. Abstract : To investigate sex and age differences in anxiety, depression, and dropout rates among patients with cardiovascular disease at baseline and following aerobic interval training-based cardiac rehabilitation (CR). Younger and middle-aged adults experience higher levels of anxiety upon entry into CR and dropout rates are highest among younger adults.